Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Perusahaan Di Bidang Konstruksi Jakarta: The Influence of Motivation and Work Discipline on Employee Performance in Construction Companies in Jakarta - Rachmawati, Susan; Syilvia, Syilvia (CV Warnak Johanna Nusantara, 2025)
Abstracts - Decreased motivation and work discipline due to delays, absenteeism, and violations of procedures, which can delay work and reduce productivity in completing work. The purpose of this study is to determine how much influence motivation and work discipline have on employee performance. This study was conducted using a descriptive quantitative approanch using statistical analysis. Data were collected by distributing questionnairs to respondents. The number of samples in this study was 38 people. This study includes data quality testing, classical, assumption testing, multiple linear regression analysis, and calculation of the coefficient of determination. The research process lasted for three mouths. The results of the data analysis showed that motivation partially affects employee performance, with a t-count value of 3,233 > t tabel 1,689. In addition, work discipline has s positive effect on performance, with a t-count value of 7,344 > 1,689. Simultaneously, through the f test, motivation work discipline simultaneously have a significant effect on employee performance, which is abtained from the f count of 44,089 > F table 3,27.